Development of Encapsulated Wasabi Flavor for Resistance in High Temperature Condition - Chintong, Sutasinee; Sukosi, Kanjana; Saengrung, Jureerat; Limpawattana, Maruj; Klaypradit, Wanwimol (Trends in Sciences, 2023)
The present work was aimed to develop encapsulated wasabi flavor beads for resistance high temperature condition. The beads prepared from waxy maize starches (HI-CAP 100), modified tapioca starches (Flavotec), alginate and chitosan at various concentrations to determine their properties. The beads size was found not significant differences in all treatments. Microcapsules of 10 % wasabi flavor derived from the mixture of HI-CAP 100 and Flavotec at mass ratio of 1:0 (w/w) and alginate and chitosan at mass ratio of 14:1 (w/w) exhibited excellent encapsulation efficiency (96.42 %) and this formulation is also demonstrated the highest retention of AITC in wasabi flavor beads after thermal process. Therefore, the encapsulated wasabi flavor has broad application prospects in food industry and development value prospects. HIGHLIGHTS The wasabi flavor encapsulation in beads and their application under heat treatment was firstly reported The findings demonstrated that the encapsulated wasabi flavor generated with t HI-CAP 100 and Flavotec at mass ratio of 1:0 (w/w) and alginate and chitosan at mass ratio of 14:1 (w/w) had capability to protect degradation of allyl isothiocyanate (AITC) under the high temperature condition This new approach will be of great benefit to the application of encapsulated wasabi flavor as an additive in the food industry GRAPHICAL ABSTRACT